“In police we trust?” - confidence in the police among adolescents with and without a migration background in Germany - Krieg, Yvonne (European journal on criminal policy and research, 2023)
Overall, adolescents exhibit a high level of confidence in the police. Nevertheless, it is problematic when certain social groups show lower levels of confidence in the police as this can affect police legitimacy. Based on a representative survey of ninth-grade students in Lower Saxony (N = 12,444), conducted in 2019, the current study examines confidence in the police among adolescents with and without a migration background. As well as an examination of the correlation, the study analyses whether the lower rate of confidence in the police among adolescents with a migration background can potentially be explained by them being exposed to a greater share and burden of influencing factors which impact confidence in the police (e.g. police contact, involvement with delinquent peers and neighbourhood characteristics). It is shown that adolescents with a migration background exhibit lower levels of confidence in the police than adolescents without a migration background. Although the correlation decreases upon the inclusion of other factors that influence confidence in the police, this relationship cannot be fully explained by the fact that young people with a migration background are also more burdened by the other determinants. However, the strongest correlations with confidence in the police are found for affinity for violence, friendship with delinquent individuals, police contact, property offenders, fear of crime and incivilities.